Buddhist Idealism, Epistemic and Otherwise: Thoughts on the Alternating Perspectives of Dharmakīrti - Arnold, Dan (Sophia, 2008)
Some influential interpreters of Dharmakīrti have suggested understanding his thought in terms of a ‘sliding scale of analysis.’ Here it is argued that this emphasis on Dharmakīrti's alternating philosophical perspectives, though helpful in important respects, obscures the close connection between the two views in play (identified by later commentators as ‘Sautrāntika’ and ‘Yogācāra’). Indeed, with respect to these perspectives as Dharmakīrti develops them, the epistemology is the same either way. Insofar as that is right, John Dunne's characterization of Dharmakīrti's Yogācāra as ‘epistemic idealism’ may not, after all, distinguish this perspective from Sautrāntika; indeed, epistemic idealism can be understood as just the view these positions share. Thus, what distinguishes the ‘Yogācāra’ section of Dharmakīrti's texts is simply his making explicit that epistemological commitments the Sautrāntika does (or at least can coherently) hold are already compatible with idealism. Sautrāntika and Yogācāra thus differ only when one turns to the metaphysical arguments that (on the idealist's view) additionally show that only such mental things as sense data could be real.